Revascularization Enhances Walking Dynamics in Patients with Peripheral Artery Disease - Farahnaz Fallahtafti; Arash Mohammadzadeh Gonabadi; Kaeli Samson; Megan Woods; Iraklis Pipinos; Sara Myers (Applied Mechanics)
Blocked or narrowed arteries restrict blood flow to the lower limbs, commonly leading to peripheral artery disease (PAD). Patients with PAD have been shown to have increased gait variability, which may contribute to higher rates of falls and worsen functional outcomes. Surgical revascularization seeks to restore blood flow to the legs, but it is unknown if this restoration enhances limb function. This study investigated whether gait variability changes in patients with PAD after revascularization surgery. Thirty-three patients with PAD exhibiting claudication symptoms were recruited for the study. Kinematic data were recorded using a motion capture system while the patients walked on a treadmill following a progressive treadmill protocol, both before and after undergoing revascularization surgery. Angular sagittal movements’ linear and nonlinear variability in the lower limbs were measured and compared before and after surgery across the ankle, knee, and hip joints. Following revascularization surgery, knee joint sample entropy (SampEn) decreased, suggesting improved gait regularity. Furthermore, the hip range of motion (ROM) significantly decreased, whereas the knee ROM significantly increased. The ankle joint showed significantly greater changes in the Lyapunov Exponent (LyE) relative to the pre-exercise condition compared with the hip and knee joints. No significant differences existed in the linear variability (standard deviation) of the ROM between joints. In individuals with PAD, revascularization surgery considerably increased knee ROM and gait regularity, indicating improved limb function and motor control. However, the ankle ROM remained unchanged, indicating the need for targeted strengthening exercises post-surgery.